'For her protection and benefit': the regulation of marriage-related migration to the UK. Issue 15 (7th December 2016) - Carver, Natasha
ABSTRACT: This paper argues that a two-tier system has evolved dividing intra-UK/EU marriages from extra-UK/EU marriages. For the former, marriage is a contract between two individuals overseen by a facilitating state. For the latter, marriage has become more of a legal status defined and controlled by an intrusive and obstructive state. I argue that this divergence in legislating regulation is steeped in an ethnicized imagining of 'Britishness' whereby the more noticeably 'other' migrants (by skin colour or religion) are perceived as a threat to the national character. The conceptualization of women as legally 'disabled' citizens (1870 Naturalisation Act) for whom a state must act as responsible patriarch, is a fundamental part of this imagining of the nation. The paper therefore examines the social (gendered and ethnicized) assumptions and political aims embedded within the legislation.